Mathematical modeling in the leaching processes of gold and copper minerals in chemical systems - Lovera Dávila, Daniel Florencio (2003)
In the present work the revision, deduction and application of mathematical models in the quantification of the reaction kinetics of leaching processes of national sulphided minerals in chemical systems is made. The interaction between the mineral particles and the leaching solution is controlled by three possible mechanisms: by chemical reaction, by diffusion through the porous bed and by mass transfer; Each mechanism has its own mathematical modeling and parametric conditions. Experimental runs of leaching of gold and copper minerals are presented, in which their kinetic control equations of the most relevant variables are shown. Other empirical models are also shown that are used to elucidate the phenomenology of the leaching of mineral species, call chalcopyrite, sphalerite and galena.